An in vitro investigation into the effects of Ritalin and Dopamine on human sperm and the functionality of the Dopamine Transporter (DAT) protein on human sperm membranes - Ferguson, Lisa Marie (Stellenbosch : Stellenbosch University, 2025)
Ferguson, L. M. 2025. An in vitro investigation into the effects of Ritalin and Dopamine on human sperm and the functionality of the Dopamine Transporter (DAT) protein on human sperm membranes. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/6325a03f-81f7-4693-8dd3-8d53428199be